A comprehensive study on the ionomer properties of PFSA membranes with confocal Raman microscopy - Maier, Maximilian; Abbas, Dunia; Komma, Miriam; Solihul Mu'min, Muhammad; Thiele, Simon; Böhm, Thomas (Journal of Membrane Science, 2023)
The proton exchange membrane is the heart of many electrochemical energy systems, and their performance and longevity depend on a careful selection and processing of membrane materials. In this work, we use confocal Raman microscopy to investigate application-relevant properties of perfluorinated sulfonic acid (PFSA) membranes. Raman spectra of Nafion, Aquivion, and 3M Ionomer at different equivalent weights show differences in the spectral area and position of various Raman bands but reveal a clear trend of band intensities versus equivalent weight. Characteristics of these ionomers such as swelling and water uptake were determined with through-plane imaging. The technique offers advantages over conventional measurements, such as contact-free and non-destructive data acquisition. Calibration curves for the equivalent weight were derived for the different PFSAs with excellent linear fits that allow a quantification of the ionizable group content. The high spatial resolution of confocal Raman microscopy of less than 2 μm enables the local evaluation of all these ionomer properties. Furthermore, Raman imaging was employed to characterize composite membranes, which shows that it can resolve individual phases and features in multi-layered membranes. This study provides a comprehensive summary of confocal Raman microscopy as a powerful tool for the analysis of ionomer and membrane properties.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Confocal Raman microscopy; Electrochemical energy systems; Imaging; Ionomer; Membrane

Communication-Proving the Importance of Pt-Interlayer Position in PEMWE Membranes for the Effective Reduction of the Anodic Hydrogen Content - Martin, Agate; Abbas, Dunia; Trinke, Patrick; Boehm, Thomas; Bierling, Markus; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard (Journal of The Electrochemical Society, 2021)
Gas crossover through the membrane poses a significant challenge to proton exchange membrane water electrolysers. This work investigates the influence of the position of platinum-based recombination interlayers integrated in the membrane on the anodic hydrogen in oxygen content. The results show that all interlayer positions reduce the anodic hydrogen content without performance losses compared to the reference without interlayer. However, an interlayer positioned closer to the anode is more effective than closer to the cathode. Further, the effect of the interlayer is more pronounced with increasing anode pressure.
CRIS-Team WoS Importer:2021-10-08